Innovation in Surabaya Zoo Management to Improve Visitor Experience - Ningrum , Elsa Wahyu; Larasati, Diyas Age; Maharani , Putri Aprilia Dwi; Wibiyanti, Annisa Delvira Putri; ZN, Risma Ayu Oktavia; Anggraini , Dilla Puspa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Aim: Study This aiming For know innovation management Garden Animals of Surabaya in increase experience visitors. Method: Research done with method descriptive qualitative through observation direct, documentation, and interviews on November 25, 2024. Result and Discussions: Research results This show that management Garden Surabaya Animals have covers various innovation, such as educational poster installation related timetable giving Eat animal For add Power pull educative for visitors, management system water absorption for prevent puddles in the cage, and the use of social media as means information and promotions. There are a number of challenges that need to be overcome handled, including not enough active some social media and conditions a number of cage that requires repair more continue, such as pen deer and pig frequent warts waterlogged. Innovation This give impact positive, good in increase welfare animals and power pull Garden Surabaya Animals as tour education. Conclusion: So that innovations implemented capable create experience more visitors positive, educative and supportive sustainability management Garden Surabaya Animals as center education and recreation.